Improving of Knowledge, Attitudes, and Practices Towards Food Safety Among Caregivers in a Child Shelter in Ecuador to Provide Safe and Nutritious Meals. (14th June 2022) - Carvajal-Aldaz, Diana; Cantos, Monica; Delgado, Maria; Gonzalez-Narvaez, Mariela
Abstract: Objectives: The aim of this study was to improve knowledge, attitudes, and practices towards food safety among caregivers for providing safe and nutritious meals to the children living in the shelter through educational interventions. Methods: Nine women in charge of the food preparation, three from the kitchen facility and six responsible for the formula preparation, were recruited in the study after signing informed consent. A specific knowledge, attitudes, and practices (KAP) survey was applied at the beginning of the study and after the educational intervention depending on the working area. The KAP survey for the three women responsible for the kitchen included 57 questions about handwashing, food preparation, food handling, food storage, and food preservation. The before and after the educational intervention results from these surveys were analyzed only with descriptive statistics due to the number of surveys applied. The KAP survey addressed the six women responsible for the formula preparation to infants included 38 questions about handwashing, formula bottle preparation, bottle sterilization, leftover formula storage, and handling of food for infants over 6 months. The responses collected before and after the educational intervention were analyzed by a Paired Student's t-test considering significant a p-value < 0.1 using the RStudio software. The educational interventions were applied to the participants to address biased or misleading information and promote safe food practices. Results: After the educational intervention of two months, the women responsible for the kitchen improved on average 29.67%, and those responsible for the formula preparation to infants had a significant improvement of 11.69% (p = 0.052). Due to the frame time available for the educational intervention being too short the participants mainly improved in knowledge. Conclusions: The educational interventions were successful to improve biased or misleading information among the caregivers and help to ensure to provide safe and nutritious meals for the children living in the shelter. Additionally, specialized safety food and safety formula bottles preparation guides with a set of safe recipes were provided to the children's shelter to help in the improvement of practices in the near future. Funding Sources: None.